Giant Asia Pacific Region E-Hailing Competitive Position During The Pandemic: A Breath Of Fresh Air For Malaysian E-Hailing Startups - Arman Hj. Ahmad; Ridzuan Masri; Chok Nyen Vui; Seena Biju; Mohd. Farid Shamsudin; Ilham Sentosa Anwar Malik (Citakonsultindo, 2023)
E-hailing service is a relative infant industry in Malaysia. Although still relatively new, its development is very rapid and is constantly evolving even during the pandemic and post-pandemic of COVID-19. However, none of the local companies became market leaders due to delays in entering the market, legalisation issues as well as the pandemic COVID-19 that caused the development of e-hailing of local start-ups are still a long way off. To drive development and become more competitive in the post-pandemic, information on the current competitive conditions of rivals is very significant so that long-term strategies can be planned and improved. This study uses a descriptive method by taking five samples of major e-hailing giants in the Asia Pacific Countries to determine their competitive position. The data consists of various up-to-date sources such as statistical data, reports, press releases, news, and company websites. All these data were analysed using several descriptive tools that are used to plan the strategic planning of the firms. Collected data were then analysed using the Competitive Profile Matrix (CPM) as the main tool used to find out the position of competing for those e-hailing companies to find out their position in various aspects by calculating the weighted average which simultaneously identifies the current market position of those e-hailing companies involved. As predicted, the competitive position of the major e-hailing players in the Asia-Pacific region has far-left domestic players in Malaysia that sadly can be considered as still in the infant stage. This paper rang the bell for the Malaysian government especially the Ministry of Transports that the very large market size and potential can be tapped by local players if the strategies are right especially in the context of promotion and effectiveness of the e-hailing apps used. Furthermore, this industry is proven to become increasingly relevant and important, especially during and after the COVID-19 outbreak, but the diversity of services needed to be enhanced by domestic players to become more relevant and competitive in both domestic and global arenas. Thus, the critical success factors need to be further identified rigorously in the future so that continuous strategic improvisation can be exercised effectively by the local Malaysian transportation operators and policymakers. This will subsequently contribute to the growth of local transportation industries and boost the local economy. Moreover, this study also provides better insight for the local transportation operators at large to explore and invest in this potential innovation of public transportation services as well as contributes to the existing knowledge on the importance of e-hailing services during the endemic in stimulating economic growth.